Apparent Interfacial Tension Effects in Protein Stabilized Emulsions Prepared with Microstructured Systems - Güell, Carme (Membranes (Basel), 2017)
Proteins are mostly used to stabilize food emulsions; however, production of protein containing emulsions is notoriously difficult to capture in scaling relations due to the complex behavior of proteins in interfaces, in combination with the dynamic nature of the emulsification process. Here, we investigate premix membrane emulsification and use the Ohnesorge number to derive a scaling relation for emulsions prepared with whey protein, bovine serum albumin (BSA), and a standard emulsifier Tween 20, at various concentrations (0.1%, 0.5%, 1.25% and 2%). In the Ohnesorge number, viscous, inertia, and interfacial tension forces are captured, and most of the parameters can be measured with great accuracy, with the exception of the interfacial tension. We used microfluidic Y-junctions to estimate the apparent interfacial tension at throughputs comparable to those in premix emulsification, and found a unifying relation. We next used this relation to plot the Ohnesorge number versus P-ratio defined as the applied pressure over the Laplace pressure of the premix droplet. The measured values all showed a decreasing Ohnesorge number at increasing P-ratio; the differences between regular surfactants and proteins being systematic. The surfactants were more efficient in droplet size reduction, and it is expected that the differences were caused by the complex behavior of proteins in the interface (visco-elastic film formation). The differences between BSA and whey protein were relatively small, and their behavior coincided with that of low Tween concentration (0.1%), which deviated from the behavior at higher concentrations.